2016
DOI: 10.1177/1078155216676631
|View full text |Cite
|
Sign up to set email alerts
|

Adherence with capecitabine: A population-based analysis based on prescription refill data

Abstract: Background Patient adherence is important with the increasing use of oral anticancer drugs. Recent studies reported different capecitabine adherence rates based on self-reporting and microelectronic monitoring of the medication bottle. Patient's awareness of being monitored may confound these results. Prescription records provide a larger and more objective dataset for adherence investigation. We report the use of computer algorithm and manual review of prescription and medical documentation to determine the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 14 publications
0
1
0
1
Order By: Relevance
“…20,21 Depending on the methods used to calculate adherence, previous studies reported compliance rates for capecitabine therapy ranging from 67.9% to 98%. 22,23 There are several ways to measure adherence levels, including self-reporting (SR), tests like the Morisky Medication Adherence Scale (MMAS-8) and the Haynes and Sackett method, 24 the therapy diary, 25 pharmacy-refill methods, 26 metabolite titration in blood or urine samples. 27,28 The latter are often considered the gold standard for adherence calculation 29,30 although, much like blood tests, they are expensive, impractical and difficult to implement.…”
Section: Introductionmentioning
confidence: 99%
“…20,21 Depending on the methods used to calculate adherence, previous studies reported compliance rates for capecitabine therapy ranging from 67.9% to 98%. 22,23 There are several ways to measure adherence levels, including self-reporting (SR), tests like the Morisky Medication Adherence Scale (MMAS-8) and the Haynes and Sackett method, 24 the therapy diary, 25 pharmacy-refill methods, 26 metabolite titration in blood or urine samples. 27,28 The latter are often considered the gold standard for adherence calculation 29,30 although, much like blood tests, they are expensive, impractical and difficult to implement.…”
Section: Introductionmentioning
confidence: 99%
“…Orak antikanser ilaçları kanser tedavisinin %25'ini oluşturmaktadır 1,2 .Oral kemoterapi ilaç kullanımı; hastalara tedavi yönetimlerinin kendi ellerinde olması, ev ortamlarında tedavi olabilmeleri, seyahat özgürlükleri, intravenöz tedavi komplikasyonlarının önlenmesi gibi pek çok avantajlar sağlamaktadır. Ancak hastaların evde bu ilaçları yeterince destek almadan kullanmalarına bağlı, yan etki yönetiminde başarısızlık, ilaç almayı unutma, ilaç alma saatlerinde uyumsuzluk, kür programını yanlış uygulama gibi ilaç uyumsuzluğuna bağlı dezavantajları da beraberinde getirmektedir [3][4][5][6][7][8][9] . Oral kemoterapi kullanımı ile onkoloji hemşiresi için tedavi uygulama yükü, evde tedaviye uyumun değerlendirilmesi, izlemi ve yan etki yönetimi değişmiştir 10 .…”
Section: Introductionunclassified